Modern systems analysis and design - Hoffer, Jeffrey A. (Pearson Prentice Hall, 2011)
The methods and principles of systems development. "Modern Systems Analysis and Design" uses a practical, rather than technical, approach to help readers learn the methods and principles of systems development. The sixth edition has been streamlined and updated to reflect the latest trends, information, and practices in the discipline.